2011
DOI: 10.2298/vsp1106523m
|View full text |Cite
|
Sign up to set email alerts
|

Occupational contact allergic dermatitis in dentistry

Abstract: Methacrylates serve as bases for acrylic resins which are used in prosthetics. Methyl methacrylate as a small molecular acrylate can permeate thin protective disposable gloves. Using adequate personal protective equipment, like nitrile rubber gloves, is the most important preventive measure in this occupation. Health practitioners should recognize possible occupational hazards in dentistry and implement appropriate preventive measures to protect health of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
(23 reference statements)
0
16
0
8
Order By: Relevance
“…[13][14][15][16] Methyl methacrylate, as a small molecular acrylate, can permeate thin protective disposable gloves; protective gloves are insufficient due to the permeability of natural rubber latex and vinyl gloves to these substances. [17][18][19][20][21] With the growing evolution of cosmetic dentistry, which exposes dental workers to resins, bleaches and adhesives, composed of acrylic-and methacrylic-based materials that can cause hand eczema, more dentists are exposed to methyl methacrylate. 3,5 Previous studies in Serbia 17 and in Valencia, Spain, 22 reported that 5-25% of dental personnel might be sensitized to methyl methacrylate, while our study revealed that 2.5% (n = 8) developed this type of allergy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] Methyl methacrylate, as a small molecular acrylate, can permeate thin protective disposable gloves; protective gloves are insufficient due to the permeability of natural rubber latex and vinyl gloves to these substances. [17][18][19][20][21] With the growing evolution of cosmetic dentistry, which exposes dental workers to resins, bleaches and adhesives, composed of acrylic-and methacrylic-based materials that can cause hand eczema, more dentists are exposed to methyl methacrylate. 3,5 Previous studies in Serbia 17 and in Valencia, Spain, 22 reported that 5-25% of dental personnel might be sensitized to methyl methacrylate, while our study revealed that 2.5% (n = 8) developed this type of allergy.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] With the growing evolution of cosmetic dentistry, which exposes dental workers to resins, bleaches and adhesives, composed of acrylic-and methacrylic-based materials that can cause hand eczema, more dentists are exposed to methyl methacrylate. 3,5 Previous studies in Serbia 17 and in Valencia, Spain, 22 reported that 5-25% of dental personnel might be sensitized to methyl methacrylate, while our study revealed that 2.5% (n = 8) developed this type of allergy. Since most of the Lebanese dentists send acrylic work to prosthetics technicians (e.g., temporary crowns, dentures, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il en résulte des cas de plus en plus nombreux de dermatites de contact aiguës qui répondent la plupart du temps à un mécanisme allergique plutôt que d'irritation [27,51].…”
Section: Allergie Aux Matériaux De Prothèseunclassified
“…Un cas d'eczéma de contact est survenu après la prise d'une empreinte avec un polyéther (Impregum®) se traduisant par des ulcérations superficielles recouvertes d'un enduit fibrinoleucocytaire et d'un érythème avec des érosions intéressant peu la fibro-muqueuse mais surtout la muqueuse libre [51].…”
Section: Allergie Aux Matériaux De Prothèseunclassified